Text and Context: Classroom as a Site of Contention (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This article presents pedagogical reflections on the experience of teaching fiction about the partition of India with Pakistan and Bangladesh and its long-lasting effects on local communities, especially along the borders. It shows how the long drawn out political movement for identity and territory, including the violence and social divisions it perpetuates, plays out in the classroom where students affected by the vestigial effects of partition encounter literature as a lived history. Using teaching strategies in this condition as a case in point, the article argues that the literature classroom can become a site of recovery and renewal, conflict and negotiation, and memory and uncovering of silenced history. The broader implications of this pedagogy for literary interpretation and classroom engagement with larger issues are further discussed.